Galileo's Dagger. (January 2016) - Anstis, Stuart
Galileo found that fine lines on a balance scale dazzled his eyes and were unreadable. So he used a grid of fine wires instead and ran his dagger across it, counting the number of auditory clicks. This is the first known experiment on sensory substitution.